The Key Determination Factors of Profitability for Banking Sector Companies - Anggita Arsyikirani; Lenni Yovita; Amalia Nur Chasanah; Vicky Oktavia (International Journal of Economics, Management and Accounting, 2025)
This study aims to analyze the factors influencing the profitability of banking companies in Indonesia, using banking ratios as independent variables. The study identifies three main variables believed to significantly impact profitability, measured by Return on Assets (ROA). The banking sector in Indonesia has been through many changes over the years. The author intends to assess the factors influencing profitability using several banking ratios. Although all three variables of banking ratios does significantly influence the rate of ROA, two of them gave negative influence to the ROA. It suggests that profitability rate is something that tend to influenced by financial ratios either positive or negative. That profitabilities influenced by influenced by the financial activity itself. The study uses regression analysis to examine the relationship between these variables and profitability. These findings provide valuable insights for bank managers and regulators to understand the factors that should be considered in efforts to improve the financial performance of banks in Indonesia. In addition, the results of this study are expected to serve as a reference for policy decisions that support the stability and growth of the banking sector in the country